Applying Systemic Approach to Develop Students’ Vocabulary - Andi Asdar (Hasanuddin University, 2018)
Systemic approach in teaching vocabulary involved aspects in learning vocabulary. The aims of this research were to observe (1) the extent to which Systemic Approach develops students’ vocabulary of the second semester of Makassar Islamic University; (2) the students’ perceptions on the application of Systemic Approach in vocabulary development. This research was carried out with second semester students of Pharmacy Department, Faculty of Mathematics and Natural Sciences, Makassar Islamic University. The research method was quasi-experimental design with pre-test, eight meetings for treatment, and post-test. Data were collected with 2 instruments: vocabulary test and questionnaire, then analyzed with statistical analysis of sample t-test and questionnaire frequency. The result of the research indicated that the p value of independent t-test comparing students’ score on post-test was p<0.05. There was a significant difference between the students treated by systemic approach compared to those without systemic approach. The questionnaire analysis indicated that the students’ perceptions on the application of Systemic Approach were positive.